Design as a Catalyst for Engaging Students in Creative Problem Solving : Final Report. - Wood, Denise; Corso, Ron; Gluth, Stuart; Scutter, Sheila; Bilsborow, Carolyn; Lindsay, Noel (Office for Learning and Teaching, 2015)
Final report from a collaborative project that addresses an identified need to support academics in the design and development of curricula in which creativity is embedded and serves as a catalyst for engaging students in the creative problem solving process. The project aims to achieve this the design, development and evaluation of a CPS framework and online CPS system which will act as a scaffold for academics in the development and redevelopment of courses, and a tool box for students designed to guide them through the creative problem solving process in their coursework. The CPS system will be open source, to enable it to be adapted by other institutions to suit their learning and teaching contexts. The project will also develop pedagogical guidelines and case studies showcasing the effective use of the CPS system. The major focus of this Innovation and Development Grant project is on curriculum renewal and innovation in learning and teaching through the use of new technologies.